2015
DOI: 10.12659/msm.893221
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Macular Peripapillary Nerve Fiber Layer and Choroidal Thickness Changes in Pregnant Women with Gestational Diabetes Mellitus, Healthy Pregnant Women, and Healthy Non-Pregnant Women

Abstract: BackgroundGestational diabetes mellitus (GDM) is a risk factor for the development of type II diabetes and it causes maternal and child morbidity. Screening for diabetic retinopathy (DR) is important because patients who develop DR have no symptoms until macular edema and/or proliferative diabetic retinopathy (PDR) are already present. The aim of this study was to determine the early retinal findings of GDM.Material/MethodsThis study was conducted in a tertiary research center. We conducted a prospective cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 26 publications
1
20
1
Order By: Relevance
“…There is limited data on this issue and to the best of our knowledge this is the first study to compare CT in pregnant women with type 1 and type 2 DM. Acmaz et al 40 reported that CT was significantly thicker in healthy pregnant women and women with GDM in comparison with non-pregnant women. However, there was no significant difference between the GDM group and the healthy pregnant women group.…”
Section: Discussionmentioning
confidence: 99%
“…There is limited data on this issue and to the best of our knowledge this is the first study to compare CT in pregnant women with type 1 and type 2 DM. Acmaz et al 40 reported that CT was significantly thicker in healthy pregnant women and women with GDM in comparison with non-pregnant women. However, there was no significant difference between the GDM group and the healthy pregnant women group.…”
Section: Discussionmentioning
confidence: 99%
“…In another similar study, Acmaz et al found that RNFL thickness, especially the nasal part, was significantly decreased in pregnant women with gestational diabetes more than in the healthy pregnant women [ 32 ]. They speculated in a similar way to ours that deterioration of the blood supply to nerves may lead to thinning of RNFL in pregnant women with gestational diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Choroidal thickness can be influenced by major factors such as age, refractive error and axial length (AL), with increasing age, AL and decreasing refractive diopter being associated with a reduction of choroidal thickness [ 23 ]. Previous authors have measured choroidal thickness during pregnancy, with conflicting results [ 16 , 24 32 ]. Different methodology may justify these different results.…”
Section: Discussionmentioning
confidence: 99%